PENGGUNAAN OBAT TRADISIONAL DALAM PENGOBATAN MALARIA DI KELURAHAN BENYOM JAYA KABUPATEN JAYAPURA - Sukriyadi Saleh; Brechkerts Lieske Angruni Tukayo; Eka Nurfadillah (As-Syifaa Jurnal Farmasi, 2023)
Traditional medicine is an active ingredient of a plant, or more than one ingredient used for treatment, as for the treatment of Malaria. Malaria is a disease caused by Plasmodium. This research was conducted to find out the use of traditional medicine for malaria treatment in Benyom Jaya Subdistrict, Jayapura Regency. This type of research was descriptive using questioner as a tool for data collecting. From the Benyom Jaya subdistrict, Jayapura Regency population, there were 87 respondents who participated in this study. The research was conducted in April 2021. The results of the study obtained characteristics of the respondent as follow, respondents mostly were in the age group 36 - 45 years (31%), male (53%), most of them had high school level of education (55%), and work as private workers (32%). The most common type of plant used by the community for antimalaria was papaya leaves with 58 respondents (48%). The reason for using traditional medicine for malaria treatment was because it was made from natural ingredients 48 respondents (41%). The processing of traditional medicine for malaria treatment was boiled by 67 respondents (71%). The place where respondents get traditional medicine for malaria treatment was in the home yard with 54 respondents (46%). Malaria usually being treated with traditional medicine among the Benyom Jaya population